Charge Immobilization of Skeletal Muscle Na(+) Channels: Role of Residues in the Inactivation Linker - Groome, James R. (The Biophysical Society, 2007)
We investigated structural determinants of fast inactivation and deactivation in sodium channels by comparing ionic flux and charge movement in skeletal muscle channels, using mutations of DIII-DIV linker charges. Charge altering and substituting mutations at K-1317, K-1318 depolarized the g(V) curve but hyperpolarized the h(∞) curve. Charge reversal and substitution at this locus reduced the apparent voltage sensitivity of open- and closed-state fast inactivation. These effects were not observed with charge reversal at E-1314, E-1315. Mutations swapping or neutralizing the negative cluster at 1314, 1315 and the positive cluster at 1317, 1318 indicated that local interactions dictate the coupling of activation to fast inactivation. Gating charge was immobilized before channel entry into fast inactivation in hNa(V)1.4 but to a lesser extent in mutations at K-1317, K-1318. These results suggest that charge is preferentially immobilized in channels inactivating from the open state. Recovery of gating charge proceeded with a single, fast phase in the double mutation K-1317R, K-1318R. This mutation also partially uncoupled recovery from deactivation. Our findings indicate that charged residues near the fast inactivation “particle” allosterically interact with voltage sensors to control aspects of gating in sodium channels.